(Bio)degradable Ionomeric Polyurethanes Based on Xanthan: Synthesis, Properties, and Structure. (24th September 2017) - Travinskaya, T. V.; Brykova, A. N.; Savelyev, Yu. V.; Babkina, N. V.; Shtompel, V. I.
Abstract : New (bio)degradable environmentally friendly film-forming ionomeric polyurethanes (IPU) based on renewable biotechnological polysaccharide xanthan (Xa) have been obtained. The influence of the component composition on the colloidal-chemical and physic-mechanical properties of IPU/Xa and based films, as well as the change of their properties under the influence of environmental factors, have been studied. The results of IR-, PMS-, DMA-, and X-ray scattering study indicate that incorporation of Xa into the polyurethane chain initiates the formation of a new polymer structure different from the structure of the pure IPU (matrix): an amorphous polymer-polymer microdomain has occurred as a result of the chemical interaction of Xa and IPU. It predetermines the degradation of the IPU/Xa films as a whole, unlike the mixed polymer systems, and plays a key role in the improvement of material performance. The results of acid, alkaline hydrolysis, and incubation into the soil indicate the increase of the intensity of degradation processes occurring in the IPU/Xa in comparison with the pure IPU. It has been shown that the introduction of Xa not only imparts the biodegradability property to polyurethane, but also improves the mechanical properties.